Shear bond strength of self-ligating orthodontic brackets on different types of porcelain crowns - Karamdeep Singh Ahluwalia; Amit Gupta; Isha Gaurav; Nitul Jain; Rakesh Garg; Nidhi Gupta (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study is to compare shear bond strength (SBS) and adhesive remnant index (ARI) of self-ligating orthodontic brackets bonded to different porcelain crowns. Materials and Methods: Three groups of different types of porcelain crowns, each containing 12 crowns were fabricated by the same technician and allocated to one of the study groups as follows: Group I - IPS porcelain crowns (Ivoclar Vivadent AG, Schaan, Liechtenstein), Group II - Porcelain fused to zirconia crowns (Zirkonzahn GmbH, Gais, Italy, Noritake Co., Tokyo, Japan) and Group III - Conventional porcelain fused to metal crowns (Ceramco3, Densply, PA, USA). The orthodontic brackets were bonded to these crowns using hydrofluoric acid (HFA) + silane etching protocol. After bonding, the SBS of the brackets were tested with a universal testing machine under standard test conditions. Results: Statistical evaluation using analysis of variance showed a significant difference between the groups (P < 0.001). The IPS group showed the highest SBS (11.58 ± 2.23 MPa) (P < 0.001). No significant difference was found between ceramo-zirconia and ceramo-metal groups (P > 0.05). Chi-square comparison revealed no significant difference in ARI scores between groups (P > 0.05). Conclusions: When HFA + silane etching protocol were used, IPS crowns showed the greatest SBS of orthodontic brackets. The ARI score was non-significant. Therefore, if there is a need to place crowns over teeth then these crowns can be used for restoration of teeth before orthodontic treatment.